The world's greatest submarines an illustrated history - Ross, David (Amber Books, 2016)
"In 1776, American Patriots attempted to destroy the British flagship Eagle using a man-operated semi-submersible, the Turtle, in New York harbor. The attack failed, but the idea stuck. Almost 90 years later, the CSS Hunley successfully attacked the Federal sloop USS Housatonic by ramming into it with a 59-kilogram (130-pound) spar torpedo. The Housatonic became the first ship in naval history to be sunk by a submarine, and so submarine warfare was born. The World's Greatest Submarines features 52 of the most significant submarines built. Each entry includes a brief description of the submarine's development and history, a color profile view or cutaway, key features and specifications. Packed with more than 200 artworks and photographs, The World's Greatest Submarines is a colorful guide for the military and naval history enthusiasts."